Hubungan Pola Asuh Orang Tua Dengan Kecerdasan Interpersonal Anak TK B di Desa Kateguhan, Tawangsari, Sukoharjo Tahun Ajaran 2015/2016 - Antisa, Avianinda Dwi; , Dr. Darsinah, M. Si (2015)
The purpose of this research is to know the correlation about parenting and interpersonal intelligent of kindergarten children in group B at Kateguhan village, Tawangsari, Sukoharjo. The research design is descriptive correlational. Population of this research is 158 children and the sample is 122 children, proportional random sampling is the method. Data of the variables come from direct questionnaire and indirect questionnaire that distributed to the parents. This research use correlation product moment for the analysis method. The result is r product moment=0,701 and sig=0,00 (p < 0,05). It means that this is a positive correlation and this correlation is significant. The conclusion is there is positive correlation significant characteristic between parent's democratic care pattern with children's interpersonal intelligent.